The Effectiveness Of a Combination Of Rosella (Hibiscus sabdariffa) and Red Ashoka (Ixora javanica) Extracts as an Eosin Substitute For Parasite Examination in Feces: Efektivitas Kombinasi Ekstrak Rosella (Hibiscus sabdariffa) dan Asoka Merah (Ixora javanica) Sebagai Pengganti Eosin Untuk Pemeriksaan Parasit pada Feses - Ahsanatul Munawwaroh; Yauwan Tobing Lukiyono; Irwan Sulisti; Agus Aan Adriansyah (Medicra (Journal of Medical Laboratory Science/Technology), 2025)
Stool examination is an important diagnostic method for detecting intestinal helminths, particularly in tropical regions like Indonesia. Eosin 2% is commonly used to enhance microscopic visualization of helminth eggs but raises concerns regarding toxicity and environmental impact. This study aimed to evaluate the effectiveness of combining roselle (Hibiscus sabdariffa) and red ixora (Ixora javanica) flower extracts as a natural substitute for eosin in stool examination. This experimental research used a post-test-only control group design with four treatment groups: eosin (positive control), and three extract concentration combinations (60%:40%, 50%:50%, and 70%:30%). The results showed that all extract combinations produced comparable contrast and clarity to eosin in visualizing helminth eggs. The Kruskal–Wallis test indicated no significant difference between treatments (p>0.05). The combination of roselle and red ixora extract can therefore be considered a potential natural alternative to eosin for stool examination without reducing microscopic effectiveness.